Inhibition of kynurenine aminotransferase II reduces activity of midbrain dopamine neurons. (March 2016) - Linderholm, Klas R.; Alm, Maximilian Tufvesson; Larsson, Markus K.; Olsson, Sara K.; Goiny, Michel; Hajos, Mihaly; Erhardt, Sophie; Engberg, Göran
Abstract: Kynurenic acid (KYNA), a neuroactive metabolite of tryptophan, is elevated in the brain of patients with psychotic disorders. Therefore, lowering brain KYNA levels might be a novel approach in the treatment of psychotic disorders. The present in vivo electrophysiological study aimed to investigate the effect of an inhibitor of kynurenine aminotransferase (KAT) II, the primary enzyme for KYNA synthesis, on dopamine (DA) neurons in the ventral tegmental area (VTA). Acute administration of the KAT II inhibitor PF-04859989 (5 or 10 mg/kg) was associated with a short-onset, time-dependent decrease in firing rate and burst activity of DA neurons, both parameters reaching a 50% reduction within 45 min. Furthermore, PF-04859989 reduced the number of spontaneously active DA cells as measured 4–6 after administration. Pretreatment withd -cycloserine (30 mg/kg) or CGP-52432 (10 mg/kg) prevented the inhibitory action of PF-04859989 (5 mg/kg) on firing rate and burst firing activity. In contrast, pretreatment with methyllycaconitine (MLA, 4 mg/kg) did not change the response, whereas picrotoxin (4.5 mg/kg) partially prevented the inhibitory effects of PF-04859989 (5 mg/kg, i.v.). Our results show that a specific inhibition of KAT II is associated with a marked reduction in VTA DA firing activity. This effect appears to be specifically executed by NMDA-receptors and mediated indirectly via a GABA(B)-receptor-induced disinhibition of DA neurons. Our findings are in line with the view that endogenous KYNA, by modulation of the NMDA-receptor, exerts important physiological roles in the brain. Highlights: Kynurenic acid is an endogenous NMDA-receptor antagonist. The role of brain kynurenic acid on firing of midbrain dopamine cells was analyzed. PF-04859989, a blocker of kynurenine aminotransferase II, inhibited firing activity. This effect is probably related to a disinhibition of GABAergic afferents. Kynurenic acid tonically regulates the firing activity of midbrain dopamine cells.